Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Krill og økosystemtokt med G.O.Sars i Sørishavet - Iversen, Svein A (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Seler brukt som "forskningsassistenter" for å utforske polhavene - Kovacs, Kit M (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Svarene på fortidens klimavariasjoner og framtidens havnivå ligger begravd i isen i Antarktis - Winther, Jan-Gunnar; Isaksson, Elisabeth (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Impacts of the Oceans on Climate Change - Reid, Philip C; Fischer, Astrid C; Lewis-Brown, Emily; Meredith, Michael P; Sparrow, Mike; Andersson, Andreas J; Antia, Avan; Bates, Nicholas R; Bathmann, Ulrich; Beaugrand, Gregory; Brix, Holger; Dye, Stephen; et al. (Advances in Marine Biology, 2009)
The oceans play a key role in climate regulation especially in part buffering (neutralising) the effects of increasing levels of greenhouse gases in the atmosphere and rising global temperatures. This chapter examines how the regulatory processes performed by the oceans alter as a response to climate change and assesses the extent to which positive feedbacks from the ocean may exacerbate climate change. There is clear evidence for rapid change in the oceans. As the main heat store for the world there has been an accelerating change in sea temperatures over the last few decades, which has contributed to rising sea‐level. The oceans are also the main store of carbon dioxide (CO2), and are estimated to have taken up ∼40% of anthropogenic-sourced CO2 from the atmosphere since the beginning of the industrial revolution. A proportion of the carbon uptake is exported via the four ocean ‘carbon pumps’ (Solubility, Biological, Continental Shelf and Carbonate Counter) to the deep ocean reservoir. Increases in sea temperature and changing planktonic systems and ocean currents may lead to a reduction in the uptake of CO2 by the ocean; some evidence suggests a suppression of parts of the marine carbon sink is already underway. While the oceans have buffered climate change through the uptake of CO2 produced by fossil fuel burning this has already had an impact on ocean chemistry through ocean acidification and will continue to do so. Feedbacks to climate change from acidification may result from expected impacts on marine organisms (especially corals and calcareous plankton), ecosystems and biogeochemical cycles. The polar regions of the world are showing the most rapid responses to climate change. As a result of a strong ice–ocean influence, small changes in temperature, salinity and ice cover may trigger large and sudden changes in regional climate with potential downstream feedbacks to the climate of the rest of the world. A warming Arctic Ocean may lead to further releases of the potent greenhouse gas methane from hydrates and permafrost. The Southern Ocean plays a critical role in driving, modifying and regulating global climate change via the carbon cycle and through its impact on adjacent Antarctica. The Antarctic Peninsula has shown some of the most rapid rises in atmospheric and oceanic temperature in the world, with an associated retreat of the majority of glaciers. Parts of the West Antarctic ice sheet are deflating rapidly, very likely due to a change in the flux of oceanic heat to the undersides of the floating ice shelves. The final section on modelling feedbacks from the ocean to climate change identifies limitations and priorities for model development and associated observations. Considering the importance of the oceans to climate change and our limited understanding of climate-related ocean processes, our ability to measure the changes that are taking place are conspicuously inadequate. The chapter highlights the need for a comprehensive, adequately funded and globally extensive ocean observing system to be implemented and sustained as a high priority. Unless feedbacks from the oceans to climate change are adequately included in climate change models, it is possible that the mitigation actions needed to stabilise CO2 and limit temperature rise over the next century will be underestimated.
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer; klimatologi

Cenozoic Climate History from Seismic Reflection and Drilling Studies on the Antarctic Continental Margin - Cooper, Alan K; Brancolini, Giuliano; Escutia, Carlota; Kristoffersen, Yngve; Larter, Rob; Leitchenkov, German; O'Brien, Phillip; Jokat, Wilfried (Developments in Earth and Environmental Sciences, 2008)
Keywords: Antarktis; geomorfologi; innlandsis; isbreer; kontinentalmargin; paleoseanografi; stratigrafi

Temperature effects on biodegradation of petroleum contaminants in cold soils - Rike, Anne Gunn; Schiewer, Silke; Filler, Dennis M (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Bioremediation in cold climates is frequently regarded with skepticism. Owners of polluted sites and regulatory agencies may doubt the effectiveness of biological degradation at near freezing temperatures. While it is true that biodegradation rates decrease with decreasing temperatures, this does not mean that bioremediation is inappropriate for cold regions. Microbial degradation of hydrocarbons occurs even around 0 °C (Chapter 4). In remote alpine, Arctic, and Antarctic locations, excavation and shipping of contaminated soil may be prohibitively expensive. Bioremediation may be the most cost-effective alternative. This chapter discusses microbial adaptation to cold temperatures as well as results of laboratory and field studies of bioremediation at low temperatures.Microorganisms can grow at temperatures ranging from subzero to more than 100 °C. Microbes are divided into four groups based on the range of temperature at which they can grow. The psychrophiles grows at temperatures below 20 °C, the mesophiles between 20 °C and 44 °C, the thermophiles between 45 °C and 70 °C, and the hyperthermophiles require growth temperatures above 70 °C to over 110 °C. The term “cold-adapted microorganisms” (CAMs) is frequently used for describing bacteria growing at or close to zero degrees Celsius. Depending on the cardinal temperatures (the minimal, the optimal, and the maximum growth temperature), CAMs can be classified as psychrophiles or psychrotrophs. Morita's (1975) definition, which holds that psychrophiles have a maximum growth temperature of less than 20 °C and an optimal growth temperature of less than 15 °C, while psychrotrophs have a maximum temperature of 40 °C and an optimal growth temperature higher than 15 °C, is widely accepted.
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Contamination, regulation, and remediation: an introduction to bioremediation of petroleum hydrocarbons in cold regions - Snape, Ian; Acomb, Larry; Barnes, David L; Bainbridge, Steve; Eno, Robert; Filler, Dennis M; Plato, Natalie; Poland, John S; Raymond, Tania C; Rayner, John L; Riddle, Martin J; Rike, Anne G; et al. (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Oil and fuel spills are among the most extensive and environmentally damaging pollution problems in cold regions and are recognized as potential threats to human and ecosystem health. It is generally thought that spills are more damaging in cold regions, and that ecosystem recovery is slower than in warmer climates (AMAP 1998; Det Norske Veritas 2003). Slow natural attenuation rates mean that petroleum concentrations remain high for many years, and site managers are therefore often forced to select among a range of more active remediation options, each of which involves a trade-off between cost and treatment time (Figure 11). The acceptable treatment timeline is usually dictated by financial circumstance, perceived risks, regulatory pressure, or transfer of land ownership.In situations where remediation and site closure are not urgent, natural attenuation is often considered an option. However, for many cold region sites, contaminants rapidly migrate off-site (Gore et al. 1999; Snape et al. 2006a). In seasonally frozen ground, especially in wetlands, a pulse of contamination is often released with each summer thaw (AMAP 1998; Snape et al. 2002). In these circumstances natural attenuation is likely not a satisfactory option. Simply excavating contaminants and removing them for off-site treatment may not be viable either, because the costs are often prohibitive and the environmental consequences of bulk extraction can equal or exceed the damage caused by the initial spill (Filler et al. 2006; Riser-Roberts 1998).
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Marine-sedimentary geology - Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Hass, Christian; Lensch, Norbert; Forwick, Matthias; Daniel, Kristin; Kober, Martin; Krüger, Stefan; Petitat, Manuel; Veit, Andreas (The Expedition ANT-XXIII/4 of the Research Vessel Polarstern in 2006, 2007)
Dynamic behaviour of the West Antarctic ice sheet in the Amundsen Sea Embayment during the later quaternary climatic cycles, pliocene to quaternary palaeoceanography in the Southwest Pacific, and holocene climate history of Maxwell Bay, King George Island.
Keywords: Sørishavet; havnivåstigning; innlandsis; klimaendringer; marin geologi; oseanografi

Kap. 4. Is og snø smelter. Kap. 5. Øyer og lavland kan drukne - Mathismoen, Ole; Ulvestad, Knut Ola (bildered.); Lie, Maya (bildered.) (Klima : hva skjer?, 2007)
Keywords: Antarktis; Sørishavet; drivhuseffekten; global oppvarming; havnivåstigning; klimaendringer

Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

Late Pan-African Fluid Infiltration in the Mühlig-Hofmann- and Filchnerfjella of Central Dronning Maud Land, East Antarctica - Engvik, Ane K; Elvevold, Synnøve (Antarctica: Contributions to Global Earth Sciences. Proceedings of the IX International Symposium of Antarctic Earth Sciences Potsdam, 2003, 2006)
Keywords: Dronning Maud Land; geologi; nunataker; petrografi

Hvalfangerselskapet Kosmos - Boye, Tore (Anders Jahres pengebinge, 2005)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

”Admiralen” til Sydishavet – et 100 års minne - Ringstad, Jan Erik (Kulturminner, 2005)
Den 21. oktober 1905 forlot flytende kokeri Admiralen og hvalbåtene Ornen og Hauken Sandefjord med kurs for Falklandsayene og Syd Shetland. Dermed innledes et nytt kapittel i den moderne hvalfangsts histone. lnitiativtaker var Christen Christensen, hovedaksjoner og disponent for Aktieselskabet "Ørnen" som eide skipene det første norske hvalfangstselskap som uttrykkelig ble startet for eventuelt innkjøp av et dampskip for innredning til koker.
Keywords: Sørishavet; historie; hvalfangstselskaper; oppdagelsesreiser; pelagisk

Flytende fabrikker – de norske hvalkokeriene - Bernhardt, Pernille Brastad (Fabrikken, 2004)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; historie; hvalfangstindustri; hvalindustri; hvalkokerier; kulturhistorie; pelagisk; sjøfolk

På hvalfangst under sovjetstjernen - Børresen, Dag Ingemar (Arbeiderhistorie, 2004)
Keywords: Nordmenn; Norge; Sørishavet; arbeiderbevegelse; arbeidsforhold; historie; hvalfangst; pelagisk; sjøfolk

"Havfruer" og sjøkvinner - Elstad, Åsa (Kystkvinner i Norge, 2004)
Keywords: Norge; Sørishavet; Vestfold; hvalfangst; kulturhistorie; pelagisk

Proterozoic–Cambrian history of Dronning Maud Land in the context of Gondwana assembly - Bauer, Wilfried; Thomas, Robert J; Jacobs, Joachim (Proterozoic East Gondwana: Supercontinent Assembly and Breakup, 2003)
Dronning Maud Land contains a fragment of an Archaean craton covered by sedimentary and magmatic rocks of Mesoproterozoic age, surrounded by a Late Mesoproterozoic metamorphic belt. Tectonothermal events at the end of the Mesoproterozoic and in Late Neoproterozoic–Cambrian times (Pan-African) have been proved within the metamorphic belt. In western Dronning Maud Land a juvenile Mesoproterozoic basement was accreted to the craton at c. 1.1 Ga. Mesoproterozoic rocks were also detected by zircon SHRIMP dating of gneisses in central Dronning Maud Land, followed by a long hiatus for which geochronological data are lacking, an amphibolite to granulite facies metamorphism and syntectonic granitoid emplacement of Pan-African age have been dated. During this orogeny older structures were completely overprinted in a sinistral tranpressive deformation regime, leading to the mainly coast-parallel tectonic structures of the East Antarctic Orogen. Putting Antarctica back in its Gondwana position, the East Antarctic Orogen continues northward in East Africa as the East African Orogen, whereas a connection to the marginal Ross Orogen at the Pacific margin of East Antarctica is suggested along the Shackleton Range. The East Antarctic-East African Orogen resulted from closure of the Mozambique Ocean and collision of West and East Gondwana, i.e. western Dronning Maud Land was part of West Gondwana. During this collision the lithospheric mantle probably delaminated, allowing the asthenosphere to underplate the continental crust and producing heat for the voluminous, typically anhydrous, Pan-African granitoids of central Dronning Maud Land.
Keywords: Dronning Maud Land; geologi

The Late Pleistocene and Holocene Glacial and Climate History of the Antarctic Peninsula Region as Documented by the Land and Lake Sediment Records- A Review - Hjort, Christian; Ingólfsson, Ólafur; Bentley, Michael J; Björck, Svante (Antarctic Peninsula Climate Variability: Historical and Paleoenvironmental Perspectives, 2003)
This chapter contains sections titled: Introduction Methods Glaciation History and the Raised Marine Shorelines Mid-Holocene Glacial Readvances The Holocene Climatic Optimum Neoglaciation and the Little Ice Age Discussion and Conclusions
Keywords: Antarktis; glasiologi; paleoglasiologi; sedimentologi

Joint marine project during NARE 200/01: dissolved oxygen and nutrient tracers in the marine Norwegian sector of the Antarctic - Fransson, Agneta; Nøst, Ole Anders; Olsson, Kristina; O'Dwyer, Jane; Drange, Helge; Børsheim, Knut Yngve; Gammelsrød, Tor; Søreide, Janne; Karlsen, Tor Ivan; Jensen, Glen (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; biogeokjemi; ekspedisjoner; marin biologi; oseanografi

Production and mortality of phytoplankton and sea-ice microalgae in the Southern ocean - Johnsen, Geir; Børsheim, Knut Yngve; Johansen, Torunn (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; Sørishavet; alger; fytoplankton; havis; marin biologi; oseanografi; sjøis; zooplankton

Studies of seals and seabirds on Bouvetøya 2000/01 - fieldwork and preliminary results - Krafft, Bjørn; Hofmeyr, Greg J G; Keith, Dave; Harck, Bianca I B; Kovacs, Kit M (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; biologi; fugler; ornitologi; seler; zoologi

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Measuring ice shelf draft and seabed topography below Fimbulisen - Nøst, Ole Anders; Goodwin, Harvey; Rønstad, Tore; Thorsen, Stein Hugo (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; glasiologi; havbunnen; isbreer; isshelf; kontinentalsokkel; topografi

Oceanographic measurements near Fimbulisen ice shelf - O'Dwyer, Jane; Nøst, Ole Anders; Karlsen, Tor Ivan; Søreide, Janne; Jensen, Glen; Fransson, Agneta; Savinov, Vladimir (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; Weddellhavet; glasiologi; hydrografi; oseanografi

Transport and transfer of organochlorines in the marine Norwegian Antarctic sector: field sampling programme during NARE 200/01 - Olsson, Kristina; Poltermann, Michael; Savinov, Vladimir; Vögele, Barbara; Kassobokova, Ksenia; Fransson, Agneta (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; marin biologi; oseanografi; plankton

Studies of population dynamics and life history strategies of Antarctic petrels at Svarthamarehn - Tveraa, Torkild; Birkeland, Ingve; Henden, John-André; Varpe, Øystein (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Den 3. Fram-ferd - Berg, Kåre (Polarskipet Fram : unik skipskonstruksjon for tre polarferder : Nansen minneforelesning 11. oktober 1999, 2001)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner

Havforskning i tung sjø - Schwach, Vera (Havet, fisken og vitenskapen: fra fiskeriundersøkelser til havforskningsinstitutt 1860-2000, 2000)
Keywords: Sørishavet; forskning; historie; hvalfangst; pelagisk

Ekspedisjonsfotografi i polare områder - Barr, Susan (Bildet lever! : bidrag til norsk fotohistorie. 7, 1999)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Roald Amundsen conquers the South Pole - Berg, Kåre (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; oppdagelsesreiser

C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Søylegangen i Buenos Aires - Fløgstad, Kjartan (Eld og vatn : nordmenn i Sør-Amerika, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Roald Amundsen; hvalfangere; hvalfangstindustri; oppdagelsesreiser; pelagisk

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Physical oceanography - Nøst, Ole Anders; Enghum, Elisabeth; Djurfeldt, Leif; Larsson, Anne-Marie (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: NARE 1997/98; Sørishavet; fysisk oseanografi

Iron enrichment with hydrocarboxylic acid and photoreduction of iron under UV and PAR: implications for phytoplankton growth in the Antarctic Ocean. Some preliminary results - Öztürk, Murat; Sakshaug, Egil (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: NARE 1997/98; Sørishavet; fytoplankton; marin biologi; oseanografi

A study of the ice dynamics of Jutulstraumen drainage area, by means of remote sensing - Rolstad, Cecilie; Hagen, Jon Ove; Østen, Kristoffer; Tonning, Tore; Semb, Svein Ingar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Antarktis; NARE 1997/98; akkumulasjon; glasiologi; innlandsis; klimaendringer

Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

“Convergence or National Styles? The Japanese Challenge to the British-Norwegian Hegemony in the Twentieth-Century Whaling Industry” - Basberg, Bjørn L (Global Markets: The Internationalization of the Sea Transport Industries since 1850, 1998)
Keywords: Antarktis; Svend Foyn; fiskeindustri; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

Sydpolen - Skattum, Ole Jacob (Roald Amundsen som geografisk oppdager, 1998)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Chemical composition in water masses and interactions with the sediment in the southern Weddel sea - Anderson, Leif G; Fogelqvist, Elisabet; Hulth, Stefan; Olsson, Kristina; Tanhua, Toste; Tengberg, Anders; Zemlyak, Frank (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; analyser; kjemisk; sedimenter; vannmasser

Geological observations in Gjelsvikfjella, Mühlig-Hogmanfjella and western Orvinfjella during NARE 96/97 - Austrheim, Håkon; Elvevold, Synnøve; Engvik, Ane K; Paulsson, Oskar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geologi

Geodetic measurements in Dronning Maud Land - Barstad, Bjørn; Eiken, Trond; Finnes, Randi; Øvstedal, Ola (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geodesi; målinger

Geodetic and topographic work - Barstad, Bjørn; Eiken, Trond; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; geodesi; topografi

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi

Et større Norge 1949-65 - Eriksen, Knut Einar (Kald krig og internasjonalisering, 1949-1965, 1997)
Keywords: Antarktis; Norge; historie; internasjonal; polarområdene; politikk; utenrikspolitikk

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Water masses in the southern Weddell Sea - Gammelsrød, Tor; Myking, Steinar; Nøst, Anders; Skagseth, Øystein; Østerhus, Svein (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; innlandsis; oseanografi; vannmasser

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Productivity in the southern Weddell Sea in the Austral summer - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum; Seim, Bjørnar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; alger; fytoplankton; krill

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Studies of seabirds and seals at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg; Dyer, Bruce M; Huyser, Onno; Næstvold, Alf (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Bouvetøya; NARE 1996/97; fugler; ornitologi; seler; zoologi

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Ice algae and phytoplankton composition in the Weddell Sea: interactions, production and nitrogen uptake - Kristiansen, Svein; Syvertsen, Erik E.; Farbrot, Tove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; alger; fytoplankton

Sea ice projects during NARE 1992/93 - Løyning, Terje Brinck; Vinje, Torgny (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; havis; sjøis

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Environmental aspects - NARE 96/97 - Njåstad, Birgit (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; Antarktistraktaten; NARE 1996/97; miljøvern

Distribution and food consumption of crabeater seals off Dronning Maud Land - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; seler; zoologi

Studies of seals in the Weddel sea and King Haakon VII sea - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; seler; zoologi

The Antarctic coastal current - physical oceanographic results from NARE 1996/97 - Nøst, Ole Anders; Lothe, Torleif (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; oseanografi

Anatomy and microbiology of the digestive tract of the Adelie penguin - Olsen, Monica Alterskjær; Mathiesen, Svein Disch (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; pingviner; zoologi

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Ice algae and phytoplankton composition in the Weddell Sea: interactions with different environmental factors - Quillfeldt von, Cecilie Hellum (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; alger; fytoplankton

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

Selvhevdelse og altruisme i Antarktis - Tamnes, Rolf (Oljealder : 1965-1995, 1997)
Keywords: Antarktis; Norge; utenrikspolitikk

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

Territoriell ekspansjonspolitikk - Fure, Odd-Bjørn (Mellomkrigstid : 1920-1940, 1996)
Keywords: Antarktis; Norge; historie; internasjonal; norske ekspedisjoner; polarområdene; politikk; utenrikspolitikk

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi

Norges polare interesser - Berg, Roald (Norge på egen hånd, 1995)
Keywords: Antarktis; Norge; historie; polarområdene; utenrikspolitikk

Modelling of Deep-Sea Gravity Currents Using an Integrated Plume Model - Alendal, Guttorm; Drange, Helge; Haugan, Peter M (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
An integrated plume model is used to describe large scale gravity currents in the ocean. The model describes competing effects of (negative) buoyancy, friction, entrainment and Cariolis farce, as well as a pressure term due to variable plume thickness, on the flux, speed and flow direction of the plume. Equations for conservation of salt and internal energy (temperature) and a full equation of state far seawater is included in the model. The entrainment of ambient water is parameterized with support in empirical data, and a drag coefficient consistent with the entrainment is introduced. The model is tested against the overflow through the Denmark Strait, the flow down the Weddell Sea continental slope, and the outflow of saline water through the Gibraltar Strait and from the Spencer Gulf, Australia. The farmer gain an extra driving mechanism due to the thermobaric effect, while in the two latter cases the initial density difference is so large that this effect is not essential. Order of magnitude fit with measurements requires drag coefficient between 0.01 and 0.1. Conditions susceptible to meander behaviour and a singularity arising from the pressure dependency on the current thickness variations are briefly discussed.
Keywords: Sørishavet; Weddellhavet; havbunnen; havstrømmer; klimamodeller; oseanografi

Detailed studies of bottom freezing under an iceshelf and mapping of accumulation by use of multi-frequency pulse-aperture radar - Erlingsson, Bjørn; Gjessing, Yngvar; Hamran, Svein Erik; Holmlund, Per (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; ekspedisjoner; georadar; isshelf; topografi

Chemical fractionation of sea salt in snow - Gjessing, Yngvar; Erlingsson, Bjørn (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; kjemisk; sjøvann; snø

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Seabird studies at Svarthamaren, Dronning Maud Land - Røv, Nils; Lorentsen, Svein-Håkon; Bangjord, Georg (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi

Proximal sub ice-shelf sedimentation Jutulgryta, East Antarctica - Solheim, Anders (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; glasiologi; isshelf

Norwegian Antarctic whaling seen through the eye of the camera - Barr, Susan (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; fotografi; historie; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk

A century of German interests in modern whaling, 1860s-1960s - Barthelmess, Klaus (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Nordmenn; Sørishavet; Tyskland; hvalfangere; pelagisk hvalfangst; økonomi

Survival against all odds? Shore station whaling at South Georgia in the Pelagic. Era, 1925-1960 - Basberg, Bjørn L (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk; økonomi; økonomisk historie

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Kapittel 3 - Arbeidsløsheten. Kapittel 6 - Den lokale organisasjonen i 30-åra - Magdahl, Jørn (Framnæsarbeidernes historie, 1993)
Keywords: Sørishavet; Vestfold; arbeiderbevegelse; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri; næringsliv

Working Conditions and Work-related Injuries and Illnesses on board Norwegian Floating Factories after World War II - Wexelsen, Einar (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Sørishavet; arbeidsforhold; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; medisin

Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

Marine biological studies in the Weddel sea and north of Dronning Maud Land - Gulliksen, Bjørn; Lønne, Ole Jørgen; Hellum, Cecilie (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; marin biologi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Marine geological studies in the Weddel sea - Sjøholm, Jorunn; Jansen, Eystein (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; marin geologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

En hvalfangstsesong med mange forlis. Den første "Kosmos" - Møller, Vilhelm (Kjære gamle Sandefjord, 1989)
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangstindustri; hvalindustri

Det siste kontinent. Roald Amundsen går ombord. Lengst mot sør - Sannes, Tor Borch (Fram, 1989)
Keywords: Antarktis; Colin Archer; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; båter; oppdagelsesreiser; polarekspedisjoner

Tekstur-estimering på LANDSAT-5 MSS opptak fra Antarktis - Albregtsen, Fritz (Proceedings fra NOBIM-konferansen 1988: Nordisk konferanse om bildebehandling og mønstergjenkjenning, Oslo, 2-3 juni 1988, 1988)
Keywords: Dronning Maud Land; informatikk; is; satellite bilder; snø

En fremtid i Antarktis? - Andersen, Rolf Trolle (Dialog Norge-Sverige: konferanser i Norges ambassade, Stockholm. 2: polarområdene, hvite felt i politikk og vitenska, 1988)
Keywords: Antarktis; forvaltning; mineraler; politikk

Sydpolen 1910-1912 - Huntford, Roland; Hoff, Truls (Roald Amundsens oppdagelsesreiser i bilder, 1988)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Early geological exploration of Seymour Island, Antarctica - Zinsmeister, William J (Geology and Paleontology of Seymour Island, Antarctic Peninsula, 1988)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Seymourøya; Vestantarktis; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Oppfinere og teknologisk utvikling i norsk hvalfangsthistorie - Basberg, Bjørn L (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; Norge; harpuner; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Da hvalfangerne organiserte seg. Forholdet mellom sosial mobilitet og organisering - Devig, Thor N (Sandefjordmuseene. Årbok, 1986)
Keywords: Sørishavet; arbeidsforhold; fagforbund; fagforeninger; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Hvalfangernes gravsteder i Antarktis - Headland, Robert K (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; historie; hvalfangere; hvalfangstindustri; hvalfangststasjoner; hvalindustri

Macrolichens of Bouvetøya - Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

The supralittoral, freshwater and terrestrial algal vegetation of Bouvetøya - Klaveness, Dag; Rueness, Jan (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; alger; botanikk

Flow and thickness of Riiser-Larsenisen, Antarctica - Orheim, Olav; Drewry, David (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Crustose lichens of Bouvetøya - Øvstedal, Dag Olav (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lichencolous ascomycetes from Bouvetøya - Øvstedal, Dag Olav; Hawksworth, David L (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Noen norske stedsnavn på Syd Georgia - Thoresen, Per (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; historie; hvalfangere; hvalfangstindustri; hvalfangststasjoner; hvalindustri

Geodetic-topographic measurements in Dronning Maud Land and on Bouvetøya - Eiken, Trond; Svendsen, Knut (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geodesi; målinger; topografi

Botany of Gjelsvikfjella and Muhlig-Hofmannfjella, Dronning Maud Land - Engelskjøn, Torstein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; planter

Hydrographic observations on the southern Weddell Sea shelf break - Foldvik, Arne; Gammelsrød, Tor (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; hydrografi; oseanografi

Circulation and Water Masses on the Southern Weddell Sea Shelf - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Bottom Currents Near the Continental Shelf Break in the Weddell Sea - Foldvik, Arne; Kvinge, Thor; Tørresen, Tor (Oceanology of the Antarctic Continental Shelf, 1985)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; kontinentalsokkel; kontinentalsokler; tidevannsstrømmer

Geological and palaeomagnetic research in Vestfjella Dronning Maud Land - Furnes, Harald; Løvlie, Reidar (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Meteorological and glaciological studies in Dronning Maud Land - Gjessing, Yngvar (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; glasiologi; meteorologi

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

Geomorphological and glaciological observations in Vestfjella, Dronning Maud Land - Jonsson, Stig (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geomorfologi; glasiologi

Iceberg research and other glaciological studies from K/V "Andenes" - Kristensen, Monica; Orheim, Olav (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; glasiologi; isfjell

Ornithological investigations in Mühlig-Hofmannfjella, Dronning Maud Land - Mehlum, Fridtjof; Bech, Claus; Haftorn, Svein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Impact of Grounded Icebergs on the Hydrographic Conditions Near the Filchner Ice Shelf - Nøst, Ole Anders; Østerhus, Svein (Ocean, Ice, and Atmosphere: Interactions at the Antarctic Continental Margin, 1985)
Keywords: Sørishavet; Weddellhavet; havis; hydrografi; isberg; isfjell; isshelf; sjøis; vannmasser

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella - Ohta, Yoshihide; Tørudbakken, Bjøn (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geologi

Sedimentological research in northwestern part of Dronning Maud Land - Olaussen, Snorre (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geologi; nunataker; sedimentologi

Marine geological studies on the Weddel Sea shelf - Solheim, Anders; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; marin geologi

Terrestrial Habitats - invertebrates - Sømme, Lauritz (Antarctica, 1985)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Terrestrial invertebrates of Mühlig-Hofmannfjella, Dronning Maud Land - Sømme, Lauritz (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; leddyr; virvelløse dyr; zoologi

Moderne hvalfangst. Fra provinsnæring til internasjonal storindustri - Wexelsen, Einar; Møller, Vilhelm (Sandar : grend og gård 1850-1970, med tidsbilder fra næringsliv og kulturhistorie, 1985)
Keywords: Sørishavet; Vestfold; hvalfangere; hvalfangstindustri; hvalindustri; kulturhistorie; pelagisk

Factors Governing Pelagic Production in Polar Oceans - Sakshaug, Egil; Holm-Hansen, Osmund (Marine Phytoplankton and Productivity: Proceedings of the invited lectures to a symposium organized within the 5th conference of the European Society for Comparative Physiology and Biochemistry — Taormina, Sicily, Italy, September 5–8, 1983, 1984)
Keywords: Sørishavet; fytoplankton; havis; krill; planteplankton; primærproduksjon; sjøis; sjøvann

Eventyret om hvalfangsten - Christensen, Nils Steen; Hagelund, Olav (Stokke bygdebok, 1983)
Keywords: Nordmenn; Sørishavet; Vestfold; arbeidsforhold; hvalfangere; hvalfangst; pelagisk

Antarktis - Greve, Tim (Australia, Oceania og Antarktis, 1982)
Keywords: Antarktis; Antarktistraktaten; Sydpolsekspedisjonen; forskning; historie; hvalfangst; oppdagelsesreiser

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner

Terrestrial vegetation of Bouvetøya : a preliminary account - Engelskjøn, Torstein (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; botanikk; ekspedisjoner; forskning

Hydrographic surveying around Bouvetøya - Fjørtoft, Jon H (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; hydrografi; oseanografi

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Geodetic determination of Bouvetøya - Fossum, Bjørn A (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geodesi

A census of penguins and seals on Bouvetøya - Haftorn, Svein; Sømme, Lauritz; Gray, John S (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; pingviner; seler; zoologi

New map of Bouvetøya - Helle, Sigurd G (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1976/77; NARE 1978/79; geodesi

Hvalfangst 1868-1914. Hvalfangst blir en ny vekstnæring - Hodne, Fritz (Norges økonomiske historie 1815-1970, 1981)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalindustri; økonomi

The glaciers of Bouvetøya - Orheim, Olav (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; glasiologi; isbreer

Geology of Bouvetøya, South Atlantic - Prestvik, Tore; Winsnes, Thore S. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geologi; vulkaner

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Bestemt på å lykkes: Amundsen på Sydpolen - Morris, Edmund (De Fryktløse : oppdagelsesferdene som endret vår verden, 1980)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser

Hvalfangst i Sørishavet - Pedersen, Arne Fevang (Kampen på havet : en krigsseilers beretning, 1980)
Keywords: Sørishavet; biografier; erindringer; historie; hvalfangere; hvalfangst; pelagisk

An eruptional model for recent lava flow on Bouvetøya, South Atlantic Ocean - Furnes, Harald; Løvlie, Reidar (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Stratigraphy and igneous petrology of Southern Heritage Range, Ellsworth Mountains, Antarctica - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S (Results from Norwegian Antarctic Research 1974-1977, 1978)
Sedimentary and magmatic rocks of Late Proterozoic to Late Paleozoic age, from the southern half of Ellsworth Mountains are described. Basic volcanic rocks, mainly agglomeratic, occur abundantly in the lower part of the succession, in the Minaret Group, and in the lower part of the Heritage Group, but are not recorded in the upper part of the Heritage Group. Due to this lithostratigraphic contrast a new classification is proposed: the Heritage Group including the Middle Horseshoe Formation and the Edson Hills Formation. A stratigraphic gap is evident above the Edson Hills Formation and a separate unit–the Dunbar Ridge Formation–is proposed. This formation is of Middle-Upper Cambrian age, with trilobite-bearing limestones. The structure is governed by a major anticline with a NW plunge in the north but almost horizontal in the south. Contrast of fold intensity and fold style below the youngest exposed unit, the Whiteout Conglomerate and a weathered surface above the Crashite Quartzite suggests a late Paleozoic deformation phase. Two phases of magmatism are distinguished. The pre-Middle Cambrian magmatism is dominantly K-alkalic and suggests the beginning of block subsidence at the early stage of a rift tectonics on a continental crust. The presumptive Late Paleozoic magmatism is N-alkalic and tholeiitic, and occurred after the main deformation; however the rocks were regionally metamorphosed in the actinolite-greenschist facies probably in late Paleozoic time. This magmatism is considered to represent an advanced stage of block tectonics. (Auth. mod.)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi; stratigrafi; vulkaner

Palaeomagnetism and morphology of lava(s) at Cape Meteor, Bouvetøya - Løvlie, Reidar; Furnes, Harald (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; geologi; vulkaner

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Sel- og hvalfangstskuter. Sydpolskipet som aldri ble bygget. Med "Southern Cross" til det sjette kontinent - Sannes, Tor Borch (Colin Archer skipene, 1978)
Keywords: Antarktis; Carl Anton Larsen; Carsten Egeberg Borchgrevink; Colin Archer; Fram (skip); Pollux (skip); Southern Cross (skip); båtbygging; båter; polarekspedisjoner; skipsbygging

Meteorological observations from Bouvetøya - Vinje, Torgny E (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1978)
Keywords: Bouvetøya; meteorologi

Weather and tide observations at Bouvetøya - Vinje, Torgny E (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi; observasjoner; oseanografi

Observations on birds and seals at Bouvetøya - Fevolden, Svein Erik; Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Bouvetøya; ekspedisjoner; fugler; pingviner; zoologi

Sydpolen - Mountfield, David; Sollie, Finn (De store polaroppdagelser, 1977)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Preliminary report of the 1976-1977 Norwegian Antarctic Research Expedition - Orheim, Olav (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; M/V Polarsirkel; NARE 1976/77; Weddellhavet; marin geofysikk; oseanografi

Observations on the snow petrel (Pagodroma nivea) in Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; fugler; ornitologi; zoologi

Hvalmål. Om lengden på blåhvalhunner fanget av norske selskaper i Antarktis - Bragstad, Torunnn (Sandefjordmuseene. Årbok, 1976)
Keywords: Sørishavet; historie; hvalfangere; hvalfangstselskaper; hvalindustri

Some observations on the geology of H. U. Sverdrupfjella, Dronning Maud Land - Hjelle, Audun (Norsk Polarinstitutt. Årbok 1972, 1974)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; stratigrafi

Internasjonale konferanser - Hva har de ført til? - Kyst-Norge], [Aksjon; Brox, Ottar (Kampen om havet, 1974)
Keywords: Sørishavet; havrett; hvalfangst; hvalfangstkvoten; internasjonal; jus; pelagisk; politikk

Hvalfangsforhandlingene i historisk og prinsipielt perspektiv: økonomi, biologi, politikk - Midgaard, Knut (Forskningspolitiske spørsmål i norsk biologi : en seminarrapport = Policy issues in Norwegian biological research : report from a seminar, 1974)
I. Vi skal i det følgende beskjeftige oss med forhandlingene om regulering av den pelagiske hvalfangst i Antarktis med sikte på å belyse to emner: 1) betingelsene for at biologers premisser skal slå igjennom i en politisk prosess som gjelder utnyttelsen av levende ressurser, 2) rollekonflikter som kan oppstå for biologer som går inn i en slik prosess. Jeg vil først gi en historikk, og så gå nærmere inn på de to emnene.
https://hdl.handle.net/11250/2486546
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Sørishavet; hvalfangstkonvensjonen; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

Diurnal variations of the surface wind over the Antarctic ice shelf - Hisdal, Vidar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Konferansepublikasjon Series B (International Union of Geological Sciences) (0332-5172)
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi

The Norwegian Antarctic Expedition 1970-1971 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1970-71; biologi; geologi; glasiologi

Corethron Criophilum Castracane: Its distribution and structure - Fryxell, Greta A; Hasle, Grethe Rytter (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; fytoplankton; marinbiologi; plankton; planteplankton

Morphologic Variability in Fasciculated Diatoms as Exemplified by Thalassiosira Tumida (Janisch) Hasle, Comb. Nov - Hasle, Grethe Rytter; Heimdal, Berit R; Fryxell, Greta A (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; Weddellhavet; alger; marinbiologi; oseanografi; plankton

The Norwegian Antarctic Expedition 1968-69 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1968, 1970)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1968-69; biologi; geologi; glasiologi

Surface snow metamorphosis on the Antarctic Plateau - Orheim, Olav (Norsk Polarinstitutt. Årbok 1966, 1968)
Keywords: Dronning Maud Land; firnsnø; glasiologi; metamorfologi; stratigrafi

Om redningen av Nordenskjøldekspedisjonen i 1904. Dengang bomben sprang - Sundt, Hans (Innen alt går i glemmeboken : erindringer og selvopplevelser fra Argentina, Chile og Uruguay, 1968)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Roald Amundsen; Sydpolsekspedisjonen; hvalfangstselskaper; oppdagelsesreiser

Antarktistraktaten = The Antarctic treaty - Utenriksdepartementet (Norges traktater, 1968)
Keywords: Antarktis; jus

Hvalfangst - Wasberg, Gunnar Christie (red.) (Sandar bygdebok, 1968)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Norske oppdagelser og rettigheter i Antarktis. Vurdering av norske territoriale og andre rettigheter i Arktis og Antarktis (En oversikt over fiske, fangst og norske polarinteresser, 1967)
Keywords: Antarktis; Bouvetøya; Norge; ekspedisjoner; fiske; hvalfangere; hvalfangst; interesser; internasjonal; oppdagelsesreiser; politikk

Tredje etappe av Dronning Maud Land Traversen - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Antarktis; ekspedisjoner; meteorologi; observasjoner

What is "Mumiyo" from Antarctica - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Dronning Maud Land; ekspedisjoner; farmakologi; fugler; ornitologi; zoologi

Fra Sydpolen til "Utilgjengelighetens pol" (From The South Pole to The Pole of Inaccessibility) - Dybvadskog, Olav (Norsk Polarinstitutt. Årbok 1964, 1966)
Keywords: Antarktis; ekspedisjoner; forskning; glasiologi; gravimetri; meteorologi; observasjoner; seismologi

Fra et besøk på Bouvetøya - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Bouvetøya; geologi; glasiologi

On the firn temperatures and glacier flow in Dronning Maud Land - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Dronning Maud Land; firnsnø; glasiologi; isbreer; isstrøm

Annen etappe av Dronning Maud Land Traversen - Orheim, Olav (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; glasiologi; gravimetri; meteorologi; seismologi

Climatological tables for Norway Station (70°30' S, 2°32' W) - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; klimatologi

Besøk på Bouvetøya i 1958 og 1966 (Bouvetøya twice visited) - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Bouvetøya; ekspedisjoner; geologi; observasjoner; topografi

Hvalfangsten - Gjermoe, Eilif (Aksjekursene i norsk skipsfart, skipsbygging og hvalfangst i mellomkrigstiden, 1964)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; næringsliv; økonomi

Traktatsamling i folkerettens alminnelige del og internasjonale organisasjoner - Bache, Mette M; Heggemsnes, Jens B (Universitetsforlaget, 1963)
Keywords: Antarktis; Antarktistraktaten 1959; jus

Den moderne hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Sørishavet; historie; hvalfangst; pelagisk

Hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Nordmenn; Sørishavet; Vestfold; historie; hvalfangere; hvalindustri; pelagisk

Note on occurence of limburgite in Dronning Maud Land, Antarctica - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1960, 1962)
The rocks from Dronning Maud Land, collected by T. LUNDE along 72° S and between 3° W and 7° E are mostly ordinary gneisses. However, a black, basaltic rock, apparently belonging to a sil! or a dyke has been found on Jutulsessen. The rock is lacking feidspar and consists only of augite, olivine, devitrified glass, and accessories. The chemical composition of the rock, mode and norm are given in table I. The present investigation shows that the Antarctic limburgite seems to be related to the normal olivine basalts, and not to the derivates of the basanite series.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi

Notes on the geology and petrology of the mountains in Fimbulheimen, Dronning Maud Land - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1961, 1962)
On the coastal slope of the great inland ice of Dronning Maud Land, Antarctica, a number of mountain peaks rises above the ice cap. The central part of the nunatak area consists of very coarse grained hornblende-biotite granite, poor in quartz and rich in porphyroblastic microcline crystals. It is cut by foliated or banded gneisses consisting essentially of the same minerals. The granite clearly intersects the gneiss, and both are cut by more fine-grained granite veins as well as by pegmatite. In some places the gneiss contains red garnet crystals, hut with one possible exception it is not proper chamockite.
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; geologi; petrologi

Nyere iakttagelser over fuglelivet på Bouvetøya - Heintz, Natascha (Norsk Polarinstitutt. Årbok 1961, 1962)
I «Informasjons-bulletin for den sovjetiske Antarktisekspedisjon», nr. 13, (1959) har G. A. SOLJANIK publisert en liten artikkel om fuglelivet på Bouvetøya. Da forfatteren har vært i land nær Kapp Circumcision hvor det tidligere, så vidt jeg kan bringe i erfaring, ikke har vært foretatt noen landing, kan det kanskje være av interesse å referere noen av de opplysningene han kommer med, ikke minst da det på en interessant måte utvider vårt kjennskap til fuglefaunaen på denne ugjestmilde øya.
Keywords: Bouvetøya; fugler; ornitologi

Absolute age determinations on rocks from Dronning Maud Land - Heintz, Natascha; Siggerud, Thor (Norsk Polarinstitutt. Årbok 1960, 1962)
Age determinations made by Belgian, Japanese and Soviet-Russian scientists on rocks from Dronning Maud Land, Antarctica are referred. These age determinations, done by different methods all indicate an age of about 500 million years for the last orogeny in this area, a result already expected on bases of geological evidence from other areas.
Keywords: Dronning Maud Land; geologi

The volume of ice in Antarctica - Liestøl, Olav (Norsk Polarinstitutt. Årbok 1961, 1962)
At present c. 15 mill. km• of the earth's surface is covered with ice. Of this area about 85 % falls to the account of Antarctica, 11 % to Greenland and c. 4 % to other areas. From this it is evident that a good knowledge of the ice mass of Antarctica is a deciding factor for the calculation of the total ice volume on earth and its effect on eustatic changes.
Keywords: Dronning Maud Land; glasiologi; havis; havnivåstigning; sjøis

Maudheim Revisited: The Morphology and Regime of the lce Shelf, 1950-1960 - Swithinbank, Charles (Norsk Polarinstitutt. Årbok 1960, 1962)
Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition, 1949-52, (71° 02' S, 10° 56' W) was revisited in January 1960 by the Norwegian Antarctic Expedition, 1956-60 under the leadership of SIGURD HELLF.. HELLE has very kindly made his observations available to me and has read the manuscript of this note. The work of his party gives a reliable measure of the accumulation of snow at Maudheim from 1952 to 1960 and allows a hetter estimate of the bottom melting on the ice shelf than was possible from the 1950-52 measurements. Air photographs taken in December 1958 by B. LuNCKE show the extent of changes in the ice front since 1951.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The cooling power in Antarctica - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1961, 1962)
We have measured the cooling power at Norway Station (70°.5 S, 2°.5 W)with kata-thermometers for air-temperature (Ta) between + 1 and –41° C, and for wind speeds (v) at 10 m leve! up to 27 m sec-1• The linear proportionality of the cooling power (H) to (36.5-Ta), for a constant wind speed, is shown to hold in this temperature-interval for a wind speed less than about 12 m sec-1• We used four kata-thermometers, and it turned out that they gave systematic different values of the cooling power for equal meteorological conditions. Comparing the individual values with their mean we find a maximum deviation of about ± 20 % . W e have supposed that this is due to errors in the calibration, subjective errors plus dissimilarities in the shape of the bulbs. The latter will cause differences in the turbulence around the bulbs, and consequently in the effective cooling of the wind. The possible difference in the cooling power of the air due to differences in the shape will probably not emerge during calibrations in a still air chamber. In spite of the dissimilar climatic conditions in Antarctica and Europe we found that a formula based upon two of our Katas, with which we have taken by far the most measurements, corresponds fairly well to the mean of the Kata-formulae found in Europe. The maximum deviation of the values given by European formulae from those derived by the Norway Station formula is about ± 20 %. We have here omitted the formula of HILL (1919), as it reveals a fairly large deviation from the other formulae.
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; meteorologi

Basal metabolic rate of “tropical” man in a polar climate - Wilson, Ove (Biometeorology: Proceedings of the Second International Bioclimatological Congress Held at the Royal Society of Medicine, London, 4–10 Sept. 1960, Organized by "The International Society of Biometeorology", 1962)
Naked man in his mode of heat regulation can be regarded as a tropical or subtropical creature with a narrow zone of adaptability, and the difference in the BMR determined in the tropics and in a temperate zone for the same individuals does not seem to exceed 10 per cent. In the climatic extremes he raises his calorific output in situations of stress but does not adapt by further changing his BMR. Some native people, however, appear to have the ability to endure a moderate cold stress without increasing their heat production above normal basal values. The metabolic determinations made by the author on the Norwegian—British–Swedish Expedition during 2 years of continuous exposure to the Antarctic climate show that there is no difference in the mean level of the BMR of white man whether he lives in a temperate or a polar climate. Other studies in cold regions support this view. Evidence of acclimatization of man to cold will not be found in the basal metabolic rate. However, the author's investigations show that the polar climate in its extreme form, as it is encountered by man in the Antarctic, can impose certain seasonal variations in the BMR. This periodicity in BMR is probably not a direct effect of climate on metabolism, but is related to it by reason of the typical activity pattern which ensues in the Antarctic climate. In agreement are the seasonal changes in BMR in the Arctic reported by Russian workers. The preliminary results of Lewis and Masterton in North Greenland, on the other hand, do not indicate a consistent seasonal variation. In changing from a temperate to a tropical climate, the BMR may vary within a narrow range of about 10 per cent, decreasing in the hot environment, but not all persons will show such a change. The seasonal variation found by the author in a polar climate is almost of the same order as the change in the tropics. It may be that the alterations in BMR caused by a change to a tropical climate are due to similar influences, which, however, do not exhibit the same seasonal incidence, because of the uniformity of the climate the year around. This implies that the basal metabolism of white man is essentially the same in all climates, but varies within a narrow range, not as a direct result of climate itself or its mean temperature, but depending upon changes in the type of activity, food, exposure, muscle tone and other factors, which are imposed by a difference in climate and regimen.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Hvalfangerne og hvalfangsten - Hjertholm, Sverre (Arbeiderbevegelsen i Vestfold : trekk fra den politiske og faglige arbeiderbevegelse 1906-1956, 1956)
Keywords: Norge; Sørishavet; Vestfold; arbeiderbevegelse; hvalfangere; hvalfangstindustri; hvalindustri

Whaling - Petersen, Kaare (The saga of Norwegian shipping : an outline of the history, growth and development of a modern merchant marine, 1955)
Keywords: Norge; Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Nitti års norsk hvalfangst - Bogen, Hans (Norge på havet, 1954)
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; skipsfart

Sandefjord og Sandar de siste 30 år - Lind, Ole (Sandefjord kommunale handelsgymnasium og handelsskole : 1904-1954, 1954)
Keywords: Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri

Sydpolen erobring - Richter, Søren (Store norske ekspedisjoner, 1954)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser

The Conquest of the South Pole - Richter, Søren (Great Norwegian expeditions, 1954)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser

Whaling - Paulsen, Harald B (Industries of Norway : technical and commercial achievements, 1952)
Keywords: Sørishavet; hvalfangstindustri; næringsliv; pelagisk

Polar Research - Sverdrup, Harald Ulrik (Industries of Norway : technical and commercial achievements, 1952)
Keywords: Antarktis; historie; norske ekspedisjoner; oppdagelsesreiser

Hvalfangerne kommer. Sammenslutningen med radiotelegrafistene. En stormakt på havet - Zachariassen, Aksel (Fra trellekår til frie menn : Norsk sjømannsforbund gjennom 40 år, 1950)
Keywords: Norge; Sørishavet; fagforeninger; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjømenn

Fangsten i nord og syd - Høeg, Ths. Arbo (Larviks sjømannsforening 1849-1949 og byens skibsfart i samme tidsrum, 1949)
Keywords: Sørishavet; Vestfold; historie; hvalfangst; hvalfangstselskaper; pelagisk

Del IV: Hvalfangst - fangstnæring - Knudtzon, Hans Thomas (Norsk fiskeri- og fangsthåndbok : saltvannsfiskeriene : ferskvannsfiskeriene : ishavsfangsten : hvalfangsten, 1949)
Keywords: Sørishavet; fiskerier; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstkvoter; hvalfangstregulering; hvalfangstselskaper; hvalindustri; internasjonal; næring; pelagisk; samarbeid; økonomi

Antarktis - Luncke, Bernhard (Norges Svalbard- og ishavs-undersøkelsers kartarbeider og anvendelsen av skrå-fotogrammer tatt fra fly, 1949)
Keywords: Antarktis; geografi; kartlegging

Norske fangfstfolk og forskere i Antarktis. Den Tredje Framferda (1910-12). Mot Nordpolen via Sørpolen. Roald Amundsen planter den norske flagget på Sørpolen 14.-12.-1911 - Opsund, Enok (Nordmenn i polheimene, 1948)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; polarområdene

Sørpolheimens geografi. Norske fangstfolk og forskere i Antarktis. Den tredje Framferda (1910-12). Mot Nordpolen via Sørpolen. Roald Amundsen planter det norske flagget på Sørpolen 14.-12.-1911 - Opsund, Enok (Nordmenn i polheimene, 1948)
Keywords: Antarktis; Norge; Roald Amundsen; Sydpol; Sydpolsekspedisjonen; forskning; hvalfangere; hvalfangst; oppdagelsesreiser

Hvalfangst på sydfeltet i krigstiden - Vikestad, Arne (Tusen norske skip : en antologi over norske sjøfolks innsats i den annen verdenskrig, 1948)
Keywords: Nordmenn; Sørishavet; Verdenskrigen 1939-45; ekspedisjoner; erindringer; hvalbåter; hvalfangst; pelagisk

Fra Spitsebergisen til Sydhavsbrisen - Stavseth, Reidar (Arven fra Bjørn Farmann : Tønsberg Sjømannsforening gjennom 100 år, 1946)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Hvalen som råvarekilde - Thon, Eivind (Råvarene i verdenshandelen : kapitler av deres historie, og kampene om dem, 1946)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalolje; økonomi

Med Lars Christensen til Antarktis - Widerøe, Viggo (Pionertid : 10 års sivilflyging i Norge, 1946)
Keywords: Antarktis; Thorshavn ekspedisjon; flyging; flyvere; kartografi; oppdagelsesreiser

Die südpolaren Gebiete - Smedal, Gustav (Souveränitätsfragen der Polargebiete : norwegische Interessen in den Eismeeren, 1943)
Keywords: Antarktis; Bouvetøya; Norge; Peter I. Øy; internasjonal; polarområdene; politikk; rett

Roald Amundsen - Wilse, Anders Beer (Norsk landskap og norske menn, 1943)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; biografier

Lengst mot sør - Arnesen, Odd (Fram : hele Norges skute, 1942)
Keywords: Antarktis; Colin Archer; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; båter; oppdagelsesreiser; polarekspedisjoner

Nordmennenes første jul i Sydishavet - Aagaard, Bjarne (Norge i Ishavet, 1941)
Keywords: Sørishavet; historie; hvalfangst

Oppdeling av polatraktene - Hoel, Adolf (Norge i Ishavet, 1941)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; internasjonal politikk; polarområdene

Rocks from the Antarctandes and the Southern Antilles - Barth, Tom. F W; Holmsen, Per; Bruun, Brynjolf (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1939)
Keywords: Antarktis; Norvegia ekspedisjonen; geologi; petrografi; petrologi

Fischerei und Fang - Johnsen, Oscar Albert (Norwegische Wirtschaftsgeschichte, 1939)
Keywords: Sørishavet; hvalfangst; pelagisk; økonomi

Meeresstrand-Enchyträiden des südlichen Atlantischen Ozeans - Michaelsen, Wilhelm (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1935)
Keywords: Antarktis; Norvegia ekspedisjoner; børsteorm; enchytreer; forskning; virvelløse dyr; zoologi

The waters of the Atlantic Antarctic Ocean - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; hydrografi; oseanografi; strømmer; vannmasser

On the Antarctic euphasiids from the "Norvegia" expeditions 1929-30 and 1930-31 - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Norvegia ekspedisjoner; euphausider; forskning; hydrografi; krill; marin biologi; plankton; zoologi

The sea-surface and the air - Mosby, Håkon (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1933)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; havoverflaten; hydrografi; meteorologi

Antarktische und antiboreale Polychaeten nebst einer Hirudinee - Augener, H (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1932)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; havbørsteormer; marin biologi; polychaeter; zoologi

Antarktiske Forskninger i ældre tid. Sydpolen naas. Flyvningere i Antarktis - Rasmussen, Knud (Polarforskningens saga. Alle tiders store opdagelsesrejser, 1932)
Keywords: Antarktis; Hjalmar Riiser Larsen; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning

Hvaler og hvalfangst - Hjort, Johan (Fra planteverden og dyreliv, 1931)
Keywords: Sørishavet; historie; hvalbestanden; hvalfangstindustri; pelagisk

Antarctic regions - Smedal, Gustav; Meyer, Chr. (Acquisition of sovereignty over polar areas, 1931)
Keywords: Antarktis; internasjonal; polarområdene; politikk; rett

Våre polarflyverferder i nord og syd - Arnesen, Odd (Til veirs på norske vinger : av flyvningens historie i Norge, 1930)
Keywords: Antarktis; Bouvetøya; Finn Lützow; Hjalmar Riiser Larsen; Holm; Nordmenn; Norge; Norvegia ekspedisjonen; biografier; historie; kartlegging; luftfart

Skibstyper - Bergh-Smith, Sverre; Jensen, J M (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalkokerier; pelagisk; skipsfart; teknologi

Antarctic and Subantarctic Actiniaria - Carlgren, Oskar (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; forskning; marin biologi; sjøanemoner; sjøroser

Rats and reindeer in the Antarctic - Olstad, Ola (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Antarktis; Norvegia ekspedisjoner; brunrotte; reinsdyr; zoologi

Om hval og hvalfangst - Risting, Sigurd (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk

Euphasiacea : with notes in their biogeography and development - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; forskning; krepsdyr; krill; marin biologi; plankton; zoologi

Mysidacea - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Norvegia ekspedisjoner; Sørishavet; forskning; krepsdyr; marin biologi; zoologi

Fangst og forskning i Sydishavet - Aagaard, Bjarne (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Carl Anton Larsen; Lars Christensen; Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Oversikt over norske hvalfangstselskaper - Haller, Geo (Red.) (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; næringsliv

Hval og hvalfangst - Risting, Sigurd (Den Norske sjøfarts historie : fra de ældste tider til vore dage, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; pelagisk; skipsfart

Om hval og hvalfangst - Risting, Sigurd (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; næringsliv; pelagisk

Moderne hvalfangst - Sørlle, Petter (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; pelagisk

I Palmer-arkipelet - Holtedahl, Olaf (H. Sørlie : 1878 27. oktober 1928, 1928)
Account of few days visit to Port Lockroy area, Graham Land, on board Norwegian whale factory ship, 1928, during "Norvegia" expedition, 1927-28.
Keywords: Antarktis; Norvegia ekspedisjonen; Vestantarktis

Sydover. Sydfeltene - Risting, Sigurd (Av hvalfangstens historie, 1922)
Keywords: Antarktis; Carl Anton Larsen; Sørishavet; fangst; historie; hvalfangere; hvalfangstindustri; hvalindustri

Aktieselskapet "Ørnen" (Vestfold fylke : Sandefjord ved 75 aars jubilæet 1920, 1920)
Keywords: Christen Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; hvalkokeri; næringsliv

Report on rock-specimens, collected on Roald Amundsen's South Pole Expedition - Schetelig, Jakob (Videnskabs-Selskabets Skrifter : 1, Mathematisk-naturvidenskabelig klasse, 1915)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; petrologi

The Voyage of the "Antarctic" to Victoria Land - Borchgrevink, Carsten Egeberg (Report of the Sixth International Geographical Congress. Held in London, 1895, 1896)
Keywords: Antarctic (skip); Antarktis; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Paa fangst i Sydishavet - Nielsen, Eivind (Sjømænd : norske Sjømænds Oplevelser : samlet fra Folkemunde og gjenfortalt, 1896)
Keywords: Carl Anton Larsen; Jason (skip); Sørishavet; ekspedisjoner; hvaler; hvalfangst; oppdagelsesreiser; pelagisk